2006
DOI: 10.1111/j.1523-536x.2006.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Supplementary Prenatal Nursing and Home Visitation Support Improve Resource Use in a Universal Health Care System? A Randomized Controlled Trial in Canada

Abstract: Additional support provided by nurses, or nurses and home visitors, can successfully address informational needs and increase the likelihood that women will use existing community-based resources. This finding was true even for high-risk women, although this intervention did not reduce the difference in resource use between high- and low-risk women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 45 publications
0
48
0
1
Order By: Relevance
“…The participants in this study are part of the longitudinal Community Perinatal Care (CPC) cohort that had been followed since pregnancy [23]. The initial sample for the CPC study included pregnant women over 18 years of age who attended one of three family physician low-risk maternity practices in the Calgary Health Region.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants in this study are part of the longitudinal Community Perinatal Care (CPC) cohort that had been followed since pregnancy [23]. The initial sample for the CPC study included pregnant women over 18 years of age who attended one of three family physician low-risk maternity practices in the Calgary Health Region.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria consisted of the inability to complete the questionnaire in English and lack of current mailing information after exhaustive searching. Findings from the original CPC study and the first two follow-up studies are reported elsewhere [23-25]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a proof of concept assessment of the efficacy of community health workers to improve childhood health outcomes, Martin et al demonstrated the positive influence of home visitations on asthma control, emergency care utilizations, and inhaler usage [41]. While similar assessment on the efficacy of home visitation techniques on food insecurity remains limited, Tough et al noted that home visitations improved nutrition counselling attendance among at-risk mothers, including those with language barriers [42]. As such, public health efforts to pilot test the efficacy of community health workers among Asian American subgroups and to create home visitation programs in order to assess food availability and increase participation in food assistance programs may help alleviate the burden of food insecurity among the most vulnerable Asian American populations.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] However, participating in multi-component programs throughout pregnancy can improve parental behaviours and use of community-based resources. 5,9 Further, reducing use of tobacco-usually included in multi-component programs-is associated with decreased risks of low birthweight and preterm birth. 10 Randomized controlled trials (RCTs) indicate that balanced energy and protein supplementation seem to reduce the This is the first observational study of Quebec's population -and one of the few worldwide -that explores the benefits of prenatal intervention along the gradient of intensity of available care.…”
Section: Introductionmentioning
confidence: 99%